Dynamics of Leaf and Root Growth: Endogenous Control versus Environmental Impact - WALTER, ACHIM (Ann Bot, 2005)
• Aims Production of biomass and yield in natural and agronomic conditions depend on the endogenous growth capacity of plants and on the environmental conditions constraining it. Sink growth drives the competition for carbon, nutrients and water within the plant, and determines the structure of leaves and roots that supply resources to the plant later on. For their outstanding importance, analyses of internal growth mechanisms and of environmental impact on plant growth are long-standing topics in plant sciences. • Scope Recent technological developments have made it feasible to study the dynamics of plant growth in temporal and spatial scales that are relevant to link macroscopic growth with molecular control. These developments provided first insights into the truly dynamic interaction between environment and endogenous control of plant growth. • Conclusions Evidence is presented in this paper that the relative importance of endogenous control versus the impact of the dynamics of the environment depends on the frequency pattern of the environmental conditions to which the tissue is exposed. It can further be speculated that this is not only relevant within individual plants (hence leaves versus roots), but also crucial for the adaptation of plant species to the various dynamics of their environments. The following are discussed: mechanisms linking growth and concentrations of primary metabolites, and differences and homologies between spatial and temporal patterns of root and leaf growth with metabolite patterns.